2020
DOI: 10.1108/nfs-02-2020-0043
|View full text |Cite
|
Sign up to set email alerts
|

Adhering to lifestyle change recommendations via the trans-theoretical model: a mixed-methods study among type 2 diabetes patients

Abstract: Purpose This paper aims to identify and explore the factors affecting type 2 diabetes mellitus (T2DM) patients' adherence to lifestyle change recommendations, with the guidance of the trans-theoretical model (stages of change). Design/methodology/approach This study was conducted in two parts. In Part A, 163 randomly selected particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…Our study showed that respondents who were using proper medicine were more likely to have good glycemic control compared to the patients not following proper medicine. This finding is supported by previous studies in diabetes, where an increase in patient compliance was associated with good glycemic control (Lee and Leung, 2003;Deiss et al, 2006;Alqudah et al, 2019;Nor et al, 2020). It has been suggested that greater effort should be made in counseling and improving compliance of patients to proper medication rather than changing the medication or altering the doses.…”
Section: Glycemic Controlsupporting
confidence: 78%
“…Our study showed that respondents who were using proper medicine were more likely to have good glycemic control compared to the patients not following proper medicine. This finding is supported by previous studies in diabetes, where an increase in patient compliance was associated with good glycemic control (Lee and Leung, 2003;Deiss et al, 2006;Alqudah et al, 2019;Nor et al, 2020). It has been suggested that greater effort should be made in counseling and improving compliance of patients to proper medication rather than changing the medication or altering the doses.…”
Section: Glycemic Controlsupporting
confidence: 78%
“…A study by [ 17 ] identified four major themes regarding adherence to lifestyle change (stumbling block, self-care belief, knowledge implementation, and self-empowerment) and advised healthcare providers to identify patients' stages of change before implementing lifestyle change. Also, Selçuk-Tosun and Zincir [ 18 ] revealed that the TTM-based motivational interview method increased the self-efficacy level of participants with type 2 DM, which helped them improve their metabolic control and health behavior stages over 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, led to improvements in both their metabolic control and overall health behaviors. Through these interviews, patients were able to identify which stage of change they were in and received personalized recommendations for lifestyle modifications [ 17 ].…”
Section: Discussionmentioning
confidence: 99%